Rupture process assessment of rock bursts in a coal mine: Inversion of source parameters and the slip distribution on the rupture surface. (December 2021) - Chen, Dong; Wang, En-yuan; Li, Nan
Highlights: Source parameters of rock burst in coal mine were obtained by Brune model. Rupture scale and average slip on the rupture surface were calculated. Slip distribution on the rupture surface of the seismic source was inversed. Accuracy of seismic source parameters and slip distribution was verified. Abstract: To assessment the source parameters and slip distribution on the rupture surface of a rock burst event in Qianqiu coal mine, and verify the accuracy of the source parameters and slip distribution on the rupture surface, four rock burst events in Qianqiu coal mine were selected for source analysis. Firstly, the source parameters of four rock burst events in Qianqiu coal mine were obtained based on the Brune model. Then, the rupture scale and average slip on the rupture surface of seismic source were identified by using the established relationship between rupture scale and moment magnitude. Finally, based on the k 2 rupture-slip model and the obtained source parameters, the slip distribution on the rupture surface was inverted to reveal the slip-rupture process of the source, and the accuracy of the seismic source parameters and the slip distribution on the rupture surface was verified based on the in-situ rupture-slip behavior. The results show that: the source parameters can be calculated using the Brune model and grid search method; the rupture scale and average slip on the rupture surface were obtained by establishing the relationship between the moment magnitude and the rupture scale of the source; based on the k 2 rupture-slip model and the scale of rupture, the slip distribution on the rupture surface of a microseismic event in a coal mine can be deduced by inversion. The calculated source parameters and slip distribution of four rock burst events are consistent with the actual records of such events in a coal mine, which further verifies the accuracy of the source parameters and slip distribution of rock burst events. These results can be used to quantify and evaluate the rupture properties, scale and process of a rock burst, and provide reference for further study of the evolution process and risk assessment of rock burst events in coal mine.